Upgrade to Pro
Continue to site
We've updated our
Privacy Policy
effective December 15. Please read our updated Privacy Policy and tap
Continue
Solutions
Integral Calculator
Derivative Calculator
Algebra Calculator
Matrix Calculator
More...
Graphing
Line Graph Calculator
Exponential Graph Calculator
Quadratic Graph Calculator
Sine Graph Calculator
More...
Calculators
BMI Calculator
Compound Interest Calculator
Percentage Calculator
Acceleration Calculator
More...
Geometry
Pythagorean Theorem Calculator
Circle Area Calculator
Isosceles Triangle Calculator
Triangles Calculator
More...
Tools
Notebook
Groups
Cheat Sheets
Worksheets
Study Guides
Practice
Verify Solution
en
English
Español
Português
Français
Deutsch
Italiano
Русский
中文(简体)
한국어
日本語
Tiếng Việt
עברית
العربية
Upgrade
Popular Problems
Topics
Pre Algebra
Algebra
Word Problems
Functions & Graphing
Geometry
Trigonometry
Pre Calculus
Calculus
Statistics
Calculations
Graphs
Popular Algebra Problems
7x^2+8x+3=0
7x^{2}+8x+3=0
3x^2-9x-84=0
3x^{2}-9x-84=0
8x^2=-128
8x^{2}=-128
solvefor y,x^2+y^2-5=2xy+y^2-5
solvefor\:y,x^{2}+y^{2}-5=2xy+y^{2}-5
0=6x^2-7x+2
0=6x^{2}-7x+2
x^2+6=8x
x^{2}+6=8x
solvefor x,x^2-15x=0
solvefor\:x,x^{2}-15x=0
9x^2+18x-27=0
9x^{2}+18x-27=0
-2x^2-2x=0
-2x^{2}-2x=0
(x-4)^2=180
(x-4)^{2}=180
roots x^2-3x-4
roots\:x^{2}-3x-4
2-(x^2-3x+8)=(2x-3)(1-x)
2-(x^{2}-3x+8)=(2x-3)(1-x)
solvefor x,xxz-250047=0
solvefor\:x,xxz-250047=0
-(y+2)(y-1)=3
-(y+2)(y-1)=3
5x^2+8=-27
5x^{2}+8=-27
100x^2+200x+100=0
100x^{2}+200x+100=0
x^2+14=-9x
x^{2}+14=-9x
36n^2-13=12
36n^{2}-13=12
144=(n+1)^2
144=(n+1)^{2}
2W^2+7W-99=0
2W^{2}+7W-99=0
4x^2-90=2x
4x^{2}-90=2x
solvefor y,4x^2-9y^2-16x-18y+7=0
solvefor\:y,4x^{2}-9y^{2}-16x-18y+7=0
completesquare x^2-5x-10
completesquare\:x^{2}-5x-10
a^2=196
a^{2}=196
factor 6x^2-13x-8=0
factor\:6x^{2}-13x-8=0
4x^2-4x-3=2
4x^{2}-4x-3=2
x^2-1=-4x
x^{2}-1=-4x
x^2+2x-32=0
x^{2}+2x-32=0
42+12x^2=0
42+12x^{2}=0
x^2+12x-14=0
x^{2}+12x-14=0
x^2=-8x-18
x^{2}=-8x-18
3x^2-1=8
3x^{2}-1=8
-15x^2+44=2
-15x^{2}+44=2
(3x^2)/2+43=139
\frac{3x^{2}}{2}+43=139
3y^2-84y=-117
3y^{2}-84y=-117
8x^2+3x+2=7x^2
8x^{2}+3x+2=7x^{2}
16=x^2-10x+25
16=x^{2}-10x+25
6x^2+108x=-582
6x^{2}+108x=-582
(x-10)(x+7)=0
(x-10)(x+7)=0
4x^2=18
4x^{2}=18
roots x^2+5x+25
roots\:x^{2}+5x+25
4(10-5x)^2=49
4(10-5x)^{2}=49
roots x^2-2x-4
roots\:x^{2}-2x-4
solvefor x,x^2+2y^2+z^2-4x+4y-2z+3=0
solvefor\:x,x^{2}+2y^{2}+z^{2}-4x+4y-2z+3=0
180+6q-4q^2=2q^2
180+6q-4q^{2}=2q^{2}
24x^2+15x=0
24x^{2}+15x=0
x^2+11x-4=0
x^{2}+11x-4=0
x^2+11x+28=70
x^{2}+11x+28=70
rationalrootstest-x^2+4x-7
rationalrootstest\:-x^{2}+4x-7
s^2-3s-10=0
s^{2}-3s-10=0
x^2+4=-5x
x^{2}+4=-5x
factor x^2-7x+10=0
factor\:x^{2}-7x+10=0
h^2-25894.4h+1336336=0
h^{2}-25894.4h+1336336=0
0=3x^2-2x-6
0=3x^{2}-2x-6
x^2+2/4-x-3/6 x=5
x^{2}+\frac{2}{4}-x-\frac{3}{6}x=5
solvefor x,s=vx+1/2 ax^2
solvefor\:x,s=vx+\frac{1}{2}ax^{2}
-8x^2+40=0
-8x^{2}+40=0
roots x^2+36x+c
roots\:x^{2}+36x+c
roots x^2+49
roots\:x^{2}+49
completesquare 4x^2+6x=12
completesquare\:4x^{2}+6x=12
roots x^2+81
roots\:x^{2}+81
a^2=5a+104
a^{2}=5a+104
2x^2-8x=-8
2x^{2}-8x=-8
roots s^2+s+6
roots\:s^{2}+s+6
3t^2-16t+28=0
3t^{2}-16t+28=0
x(2x-1)=120
x(2x-1)=120
4z^2-100=-80
4z^{2}-100=-80
completesquare x^2-5x+5/4
completesquare\:x^{2}-5x+\frac{5}{4}
-1/5 x^2+20=0
-\frac{1}{5}x^{2}+20=0
8x^2-5x-3=0
8x^{2}-5x-3=0
x+1=10x^2
x+1=10x^{2}
solvefor a,(a-b)^2=0
solvefor\:a,(a-b)^{2}=0
2c^2+14c+10=-3
2c^{2}+14c+10=-3
r^2-10+25=1
r^{2}-10+25=1
factor 2x^2-6=11
factor\:2x^{2}-6=11
2x+3=x^2+x+1
2x+3=x^{2}+x+1
roots 2x^2+2x+1
roots\:2x^{2}+2x+1
x^2+(x-1)^2=1
x^{2}+(x-1)^{2}=1
(x+20)^2=625
(x+20)^{2}=625
x^2-(2x+1)^2=-21
x^{2}-(2x+1)^{2}=-21
0=-0.04x^2+0.8x+9
0=-0.04x^{2}+0.8x+9
4x^2-15x+14=0
4x^{2}-15x+14=0
x^2-10=4x+11
x^{2}-10=4x+11
47y^2=-15y
47y^{2}=-15y
x^2-10x+45=0
x^{2}-10x+45=0
completesquare x^2+8x=-7
completesquare\:x^{2}+8x=-7
0=12x^2-28x+12
0=12x^{2}-28x+12
(4-x)(1-x)+2=0
(4-x)(1-x)+2=0
2z^2+2.5z+3.75=0
2z^{2}+2.5z+3.75=0
6x^2=29x+5
6x^{2}=29x+5
2x(x-3)=x^2-9
2x(x-3)=x^{2}-9
-x^2+6x+3=x+3
-x^{2}+6x+3=x+3
4x^2+x+12=0
4x^{2}+x+12=0
factor 5x^2-37x-24=0
factor\:5x^{2}-37x-24=0
factor 8x^2+2x-1=0
factor\:8x^{2}+2x-1=0
5(5x-6)^2-27=18
5(5x-6)^{2}-27=18
3x^2+5x+1=0
3x^{2}+5x+1=0
a^2=-5a+6
a^{2}=-5a+6
(60-3x)\times (32-x)=480
(60-3x)\times\:(32-x)=480
-x^2=12
-x^{2}=12
1
..
4584
4585
4586
4587
4588
..
4737